2022
DOI: 10.1371/journal.pone.0265928
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressants and health-related quality of life (HRQoL) for patients with depression: Analysis of the medical expenditure panel survey from the United States

Abstract: Background Despite the empirical literature demonstrating the efficacy of antidepressant medications for treatment of depression disorder, these medications’ effect on patients’ overall well-being and health-related quality of life (HRQoL) remains controversial. This study investigates the effect of antidepressant medication use on patient-reported HRQoL for patients who have depression. Methods A comparative cohort, secondary database analysis was conducted using data from the United States’ Medical Expendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 34 publications
0
35
0
1
Order By: Relevance
“…Finally, the effect of antidepressants on HRQoL might not be as sustained at 12- or 24-month follow-up. Consistent to this explanation, a recent study in patients with MDD comparing a cohort with and without intake of antidepressants ( 43 ) showed that the real-world effect of antidepressant intake does not continue to improve patients’ HRQoL over time, and the effect of antidepressants on improvements of HRQoL was limited to the initial 2–3 months of treatment. However, the HRQoL scores did not sufficiently improve in long-term compared to the general population ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 89%
“…Finally, the effect of antidepressants on HRQoL might not be as sustained at 12- or 24-month follow-up. Consistent to this explanation, a recent study in patients with MDD comparing a cohort with and without intake of antidepressants ( 43 ) showed that the real-world effect of antidepressant intake does not continue to improve patients’ HRQoL over time, and the effect of antidepressants on improvements of HRQoL was limited to the initial 2–3 months of treatment. However, the HRQoL scores did not sufficiently improve in long-term compared to the general population ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 89%
“…Hence proof via randomized data is missing. Some observational data on quality of life do not show notable benefit with antidepressants 44 …”
Section: From Research To Clinical Practicementioning
confidence: 98%
“…Some observational data on quality of life do not show notable benefit with antidepressants. 44 Lithium is different from most other psychiatric drugs (outside of the mood stabilizer class of lamotrigine and valproate and carbamazepine) in that it has clear randomized data that it improves course of illness (prevents episodes), extends life, and prevents hospitalizations. 33 Such randomized data do not exist in long-term studies, meaning 1 year or longer, with antidepressants for unipolar depression, antipsychotics for schizophrenia, or anxiolytics for anxiety conditions.…”
Section: From Research To Clinical Practicementioning
confidence: 99%
“…Zarážející je informace britských autorů Cruickshanka, MacGillivraye a Bruce (2008), jejichž výzkum poukázal, že odhadem asi třetina lidí ve Velké Británii, užívajících antidepresiva déle než dva roky, již nenaplňuje žádnou klinickou indikaci k dlouhodobému podávání medikace, opírající se o důkazy. A jiná metaanalýza zase ukazuje, že kvalita života pacientů v dlouhodobé medikaci antidepresivy se nevylepšuje oproti neléčeným kontrolám (Almohammed et al, 2022). V tomto bodě budeme potřebovat pečlivé dlouhodobé studie i kazuistické záznamy, abychom lépe porozuměli podstatě dlouhodobého podávání antidepresiv.…”
Section: Tabulkaunclassified